Quantifying bed‐related suspended load in gravel bed rivers through an analysis of the bedload‐suspended load relationship. Issue 9 (25th April 2019) - Misset, C.; Recking, A.; Navratil, O.; Legout, C.; Poirel, A.; Cazilhac, M.; Briguet, V.; Esteves, M.
Abstract: Suspended load transport can strongly impact ecosystems, dam filling and water resources. However, contrary to bedload, the use of physically based predicting equations is very challenging because of the complexity of interactions between suspended load and the river system. Through the analysis of extensive data sets, we investigated extent to which one or several river bed or flow parameters could be used as a proxy for quantifying suspended fluxes in gravel bed rivers. For this purpose, we gathered in the literature nearly 2400 instantaneous field measurements collected in 56 gravel bed rivers. Among all standard dimensionless parameters tested, the strongest correlation was observed between the suspended sediment concentration and the dimensionless bedload rate. An empirical relation between these two parameters was calibrated. Used with a reach average bedload transport formula, the approach allowed to successfully reproduce suspended fluxes measured during major flood events in seven gravel bed alpine rivers, morphodynamically active and distant from hillslope sources. These results are discussed in light of the complexity of the processes potentially influencing suspended load in a mountainous context. The approach proposed in this paper will never replace direct field measurements, which can be considered the only confident method to assess sediment fluxes in alpine streams; however, it can increment existing panel tools that help river managers to estimate even rough but not unrealistic suspended fluxes when measurements are totally absent. © 2019 John Wiley & Sons, Ltd. Abstract : An analysis of a large data set comprising nearly 2400 instantaneous values in 56 gravel bed rivers reveals that dimensionless bedload rate is the best available macro descriptor for suspended load availability in that kind of streams. Using this descriptor permits to reproduce successfully the suspended load measured in seven alpine rivers. We conclude that dimensionless bedload rate offers valuable perspective for suspension prediction in alluvial sections, considered not too close from highly eroded hillslopes, and especially for major events.